Slovak Republic : 2018 Article IV Consultation-Press Release; Staff Report and Statement by the Executive Director for the Slovak Republic. (IMF Staff Country Reports; Country Report ;, 2018)
The Slovak economy is enjoying consecutive years of favorable performance marked by robust real per capita GDP growth, record-low unemployment and sustained improvement in fiscal balances. However, shortages of skilled labor, and gaps in education and institutional quality pose risks to an already declining productivity growth. A decade-long double-digit mortgage lending growth has more than doubled household indebtedness relative to GDP, posing financial stability risks.